2022
DOI: 10.1021/acssuschemeng.2c04422
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive and Efficient Peptide Delivery by a Novel Biocompatible Ionic Liquid

Abstract: The application of bioactive polypeptides has become a challenge in the pharmaceutical industry. Copper glycyl-histidine-tripeptide (GHK-Cu) exerts various biological effects, including antioxidation, promotion of cell proliferation, and enhancement of repair. However, its clinical application is restricted by its hydrophilicity and severe demands with respect to the delivery conditions. Therefore, for the purpose of its application and of resolving the existing issues of GHK-Cu, we designed and developed a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Previous reports showed that enzymes of widely divergent types can maintain their activities in ILs or aqueous biphasic IL systems. 21,22 ILs have also been used in electrochemical biosensors, 23 drug delivery 24 and cancer treatment. 25 In addition, ILs can be tuned to improve one or several of their properties by combining appropriate ions or by functionalizing their organic moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that enzymes of widely divergent types can maintain their activities in ILs or aqueous biphasic IL systems. 21,22 ILs have also been used in electrochemical biosensors, 23 drug delivery 24 and cancer treatment. 25 In addition, ILs can be tuned to improve one or several of their properties by combining appropriate ions or by functionalizing their organic moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Transdermal delivery entails the delivery of drugs through dermal absorption to the site of action to achieve systemic or local therapeutic effects for the prevention or treatment of diseases. [ 12 ] Compared with other modalities, dermal absorption has many advantages, such as increased patient compliance, continuous drug release to increase and maintain blood concentrations, and avoiding first‐pass metabolism that protects sensitive drugs from adverse conditions in the gastrointestinal tract and reduces gastrointestinal irritation. [ 13 ] A major obstacle to transdermal drug delivery is the skin itself, whose outermost dense stratum corneum (SC) consists of keratin‐rich cells embedded in multiple lipid bilayers, and whose low permeability severely limits the transmission of most drug molecules.…”
Section: Introductionmentioning
confidence: 99%